Is Australia weird? A cross-continental comparison of biological, geological and climatological features - Flores-Moreno, Habacuc; Dalrymple, Rhiannon L.; Cornwell, Will K.; Popovic, Gordana; Nakagawa, Shinichi; Atkinson, Joe; Cooke, Julia; Laffan, Shawn W.; Bonser, Stephen P.; Schwanz, Lisa E.; Crean, Angela J.; Eldridge, David J.; et al. (Frontiers in Ecology and Evolution, 2023)
1 Australia’s distinctive biogeography means that it is sometimes considered an ecologically unique continent with biological and abiotic features that are not comparable to those observed in the rest of the world. This leaves some researchers unclear as to whether findings from Australia apply to systems elsewhere, (or vice-versa), which has consequences for the development of ecological theory and the application of ecological management principles. We analyzed 594,612 observations spanning 85 variables describing global climate, soil, geochemistry, plants, animals, and ecosystem function to test if Australia is broadly different to the other continents and compare how different each continent is from the global mean. We found significant differences between Australian and global means for none of 15 climate variables, only seven of 25 geochemistry variables, three of 16 soil variables, five of 12 plant trait variables, four of 11 animal variables, and one of five ecosystem function variables. Seven of these differences remained significant when we adjusted for multiple hypothesis testing: high soil pH, high soil concentrations of sodium and strontium, a high proportion of nitrogen-fixing plants, low plant leaf nitrogen concentration, low annual production rate to birth in mammals, and low marine productivity. Our analyses reveal numerous similarities between Australia and Africa and highlight dissimilarities between continents in the northern vs southern hemispheres. Australia ranked the most distinctive continent for 26 variables, more often than Europe (15 variables), Africa (13 variables), Asia (12 variables each), South America (11 variables) or North America (8 variables). Australia was distinctive in a range of soil conditions and plant traits, and a few bird and mammal traits, tending to sit at a more extreme end of variation for some variables related to resource availability. However, combined analyses revealed that, overall, Australia is not significantly more different to the global mean than Africa, South America, or Europe. In conclusion, while Australia does have some unique and distinctive features, this is also true for each of the other continents, and the data do not support the idea that Australia is an overall outlier in its biotic or abiotic characteristics.